Data Berkualitas, Keputusan Cerdas: Rahasia Sukses Bisnis Modern - Salsabil, Hafiz; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Abstract Quality data is a key foundation for making accurate, effective and strategic business decisions in today's digital era. With the increasing complexity of the business environment and the ever- increasing volume of data, companies face major challenges in ensuring that the data used is valid, complete, consistent and reliable. This article takes an in-depth look at the importance of data quality in the modern business context, including how high-quality data can improve operational efficiency, strengthen customer relationships, and provide a sustainable competitive advantage. It also outlines the negative impacts that can arise from using poor quality data, such as decision- making errors, financial losses, and reputational risks. Furthermore, various strategies and best practices to improve data quality are discussed in detail, ranging from data validation and cleansing, metadata management, human resource training, to the utilization of automation technology. With the right understanding and implementation of data quality management, organizations can optimize data-driven decision-making processes, accelerate responses to market changes, and create significant added value to the business. This article is expected to be an important reference for business practitioners, academics, and policy makers in managing data as a strategic asset to achieve success.